2018
DOI: 10.5350/sleep.hypn.2019.21.0182
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Stress and its Relation to Insomnia among Nurses of Educational Hospitals in Qazvin

Abstract: Stress is an inevitable part of life. It is a universal phenomenon and general experience of human which is necessary for his/ her survival and growth. It affects everyone irrespective of age, gender, race, economical condition or educational level. Although stress can be natural and necessary, if it is strict, continuous and repetitious and an individual is not able to respond to it effectively or if supportive sources are limited, it becomes a negative phenomenon which brings about physical and psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There are 9 subscales, namely death and dying (questions no. 1, 9, 17, 27, 37, 47, 53), conflict with physicians (2,10,28,38,48), inadequate emotional preparation (3,11,19), problems relating to peers (4,12,20,21,22,50), problems relating to supervisors (5,30,31,40,46,49,54), work load (13,23,32,41,42,45,51,55,57), uncertainty concerning treatment (6,14,18,24,29,33,36,39,43) patients and their families (7,15,25,34,35,44,52,56), and discrimination (8,16,26). In all cases, the fifth alternative answer "does not apply" must be scored as 0.…”
Section: Demographicmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 9 subscales, namely death and dying (questions no. 1, 9, 17, 27, 37, 47, 53), conflict with physicians (2,10,28,38,48), inadequate emotional preparation (3,11,19), problems relating to peers (4,12,20,21,22,50), problems relating to supervisors (5,30,31,40,46,49,54), work load (13,23,32,41,42,45,51,55,57), uncertainty concerning treatment (6,14,18,24,29,33,36,39,43) patients and their families (7,15,25,34,35,44,52,56), and discrimination (8,16,26). In all cases, the fifth alternative answer "does not apply" must be scored as 0.…”
Section: Demographicmentioning
confidence: 99%
“…A study in China revealed that 73.5% of nurses had work-related stress (4). In the Middle East, more than 90% of nurses working at Qazvin hospital in Iran suffered high levels of stress (5). In a South African study, there were 86% of nurses got stressed due to financial problem, 58% experienced high levels of work stress related to staffing issues, 65% got fatigued related to lack of personal achievement, 66% experienced low job satisfaction related to pay, and 60% reported poor general health because of anxiety and insomnia (6).…”
Section: Introductionmentioning
confidence: 99%